2010
DOI: 10.1097/wno.0b013e3181d8e4af
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon Alpha-Associated Optic Neuropathy

Abstract: A 52-year-old man with chronic hepatitis C presented with painless, bilateral, simultaneous non-arteritic anterior ischemic optic neuropathy (NAION) and peripheral neuropathy. Symptoms began 19 weeks after starting peginterferon alpha-2a. The peripheral neuropathy and vision of the right eye improved, but the vision of the left eye worsened after stopping interferon. We identified 23 additional cases of NAION during interferon alpha therapy. At least 12 of these patients suffered bilateral NAION. Patients lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…It was reported that a hepatitis C patient treated with interferon and ribavirin presented with bilateral, simultaneous NAION. 16 The authors also observed bilateral paresthesia in both hands and feet, reinforcing the hypothesis of a systemic toxicity. Both interferon and ribavirin were discontinued.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It was reported that a hepatitis C patient treated with interferon and ribavirin presented with bilateral, simultaneous NAION. 16 The authors also observed bilateral paresthesia in both hands and feet, reinforcing the hypothesis of a systemic toxicity. Both interferon and ribavirin were discontinued.…”
Section: Discussionmentioning
confidence: 52%
“…This suggested that NAION could be a rare association of interferon/ribavirin therapy, considering that a number of cases might not have been reported. 16 Among these 23 cases, 12 patients were treated with interferon and ribavirin, and 11 patients with interferon alone. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 5 The reported cases of NAION with ribavirin were when it was used in combination with interferon, which alone has been associated with NAION. 3 There are two reported cases of NAION occurring in HCV patients with no other risk factors. 6 , 7 Our patient, however, had just completed his six month course of anti-viral treatment prior to his NAION presentation, making HCV infection an unlikely causative agent.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Additionally, pharmaceutical agents including phosphodiesterase-5 inhibitors and interferons have been linked to NAION occurrence. 2 , 3 Interferon therapy, however, has largely been replaced with newer hepatitis C treatment modalities. Harvoni (ledipasvir/sofosbuvir) is a combination of viral polymerase and protein function inhibitors which recently was FDA-approved for hepatitis C treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although it may be effective in treating the eye disease in Behcet's disease it also has ocular side effects which are much more commonly seen in patients receiving interferon with ribavarin for hepatitis C infection [70]. The include cotton wool spots in the nerve fibre layer of the retina which are harmless abut sight loss can also occur from optic nerve involvement [71].…”
Section: Biological Agentsmentioning
confidence: 99%